Van Hiele's Theory and Think Pair Share Cooperative Learning Model and Their Effect on Madrasah Tsanawiyah Student's Level of Mathematical Thinking - Arif Muchyidin; Toto Syatori Nasehudin; Vivi Fitri Falentina (Journal of General Education and Humanities, 2022)
This study aimed to determine the effect of applying van Hiele's theory using a Think Pair Share (TPS) cooperative learning model on students' mathematical thinking levels. Following the research objectives, the researchers used experimental and quantitative research methods. In this study, two sampling techniques were used, namely using, purposive and random samples. Based on the sampling technique, class VIII F is the experimental class, and class VIII G is the control class, with 32 students each. Based on the results of the analysis, it was found that the level of students' mathematical thinking after the implementation of van Hiele's theory used the TPS type cooperative learning model with an average post-test score of 63.38, which was considered sufficient, and based on the results of hypothesis testing using t-test calculations, t-count = 3.825 > t-table = 2.04. This means that applying van Hiele's theory utilizing a Think Pair Share (TPS) cooperative learning model affects the level of students' mathematical thinking.